Revision of the Chinese species of Andropromachus Carl, 1913 (Phasmatodea, Lonchodidae, Necrosciinae) - Gao, Hao-Ran; Huang, Jun-Kai; Wang, Chen; Xie, Chong-Xin; Li, Yong-He (Zootaxa, 2022)
A new species Andropromachus ynau sp. nov.. is described and the Chinese species of the moss-like stick insect genus Andropromachus are reviewed. An updated key to the known species of this genus is provided. Types of the new species are deposited in Yunnan Agricultural University (YNAU).